Pembiasaan Nilai-Nilai Al-Qur’an di Lingkungan MTs Miftahul Falaah: Studi Living Qur’an - Hidayah, Tarisa Amaliana; Wahyudin, Muhammad; Kurniawan, Ade; In, Ummi Nurul; Anwar, Muftirotul; Nisa, Lia Rislatin; Hakamah, Zaenatul (Canonia Religia, 2024)
This article aims to reveal the implementation of the Qur'anic values indoctrination program at MTs Miftahul Falaah as an effort to develop character-based education in the madrasah. In their daily activities, students are required to participate in various activities that internalize the values of the Qur'an, including duha prayer, congregational zuhr prayer, recitation of Surah Yasin and several short surahs in class, study sessions of the book Waṣaya al-Abā’i li al-Abnā’i as well as Quranic reading and writing learning (BTQ). These habits are carried out according to a predetermined schedule, except for congregational prayers which are performed daily. This study focuses on two aspects: the implementation of Qur'anic values and their role in shaping the religious character of students.  Therefore, this research aims to reveal religious routines which are part of the living Qur'an phenomenon in the context of the educational environment, specifically in MTs Miftahul Falaah. The study involves field research and is examined using the living Qur'an approach. The results of this research indicate that the application of Qur'anic values in the environment of MTs Miftahul Falaah is a conscious and planned effort to prepare students to recognize, understand, internalize, and practice the values contained in the Qur'an. This initiative significantly contributes to the development of students' religious character by instilling obedience to Islamic teachings, be tolerant, and possess noble manners (akhlāk al-karīmah).